2022
DOI: 10.1371/journal.pgen.1010127
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite regeneration in C. elegans is controlled by the RAC GTPase CED-10 and the RhoGEF TIAM-1

Abstract: Neurons are vulnerable to physical insults, which compromise the integrity of both dendrites and axons. Although several molecular pathways of axon regeneration are identified, our knowledge of dendrite regeneration is limited. To understand the mechanisms of dendrite regeneration, we used the PVD neurons in C. elegans with stereotyped branched dendrites. Using femtosecond laser, we severed the primary dendrites and axon of this neuron. After severing the primary dendrites near the cell body, we observed sprou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 77 publications
2
29
0
Order By: Relevance
“…Since the RNAi mediated knockdown of mec-3, tiam-1 and hpo-30 produced strong phenotype in nre1(-) lin-15b(-) , Pmec-3::sid-1[+] strain, we were encouraged to test whether one can optimally use this background in dendrite regeneration studies. Previous work showed that the primary dendrite of PVD upon laser injury shows regeneration response (15, 17). The dendrite regeneration depends on the RAC GTPase CED-10, GEF TIAM-1 (17) and the fusogen molecule AFF-1 (16).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the RNAi mediated knockdown of mec-3, tiam-1 and hpo-30 produced strong phenotype in nre1(-) lin-15b(-) , Pmec-3::sid-1[+] strain, we were encouraged to test whether one can optimally use this background in dendrite regeneration studies. Previous work showed that the primary dendrite of PVD upon laser injury shows regeneration response (15, 17). The dendrite regeneration depends on the RAC GTPase CED-10, GEF TIAM-1 (17) and the fusogen molecule AFF-1 (16).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that the primary dendrite of PVD upon laser injury shows regeneration response (15,17). The dendrite regeneration depends on the RAC GTPase CED-10, GEF TIAM-1 (17) and the fusogen molecule AFF-1 (16).…”
Section: Rnai In Nre1(-) Lin-15b(-) Pmec-3::sid-1[+] Backgroundmentioning
confidence: 97%
See 2 more Smart Citations
“…Although TIAM-1 is a GEF factor, its GEF activity is not required for normal dendritic development [ 46 ]. Instead, a recent study showed the GEF activity of TIAM-1 is required for dendritic regeneration after laser ablation [ 47 ]. Here, we further show that TIAM-1 patterns neuronal development through its different domains: N-terminal EVH1 domain, middle PDZ domain, C-terminal GEF domain.…”
Section: Introductionmentioning
confidence: 99%